2006
DOI: 10.1103/physrevb.73.245408
|View full text |Cite
|
Sign up to set email alerts
|

NO structures adsorbed on Rh(111): Theoretical approach to high-coverage STM images

Abstract: Theoretical modeling of scanning tunneling microscopy ͑STM͒ measurements is used for the interpretation of images of nitrogen monoxide on Rh͑111͒ surfaces in order to gain insight into the factors which control the contrast of an STM image, especially in the case of high coverage overlayers. Topographic images of NO/Rh͑111͒ for different coverages and adsorption positions were calculated. These results were used to analyze the experimental images obtained for the p͑2 ϫ 2͒-3NO and p͑3 ϫ 3͒-7NO high coverage str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 44 publications
(51 reference statements)
7
24
0
Order By: Relevance
“…The one instance of altered site preference is for Ir(111), and this can be explained by the very close spacing of uncorrected E chem values on that surface. Qualitatively, our results for site preference are in agreement with previous theoretical results [16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][41][42][43][44][45][46][47]. Quantitatively, the values of E corr chem reported here may be more reliable, and in particular the relative values of E corr chem at different sites on the same metal may be important for interpreting how chemisorption evolves with coverage.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The one instance of altered site preference is for Ir(111), and this can be explained by the very close spacing of uncorrected E chem values on that surface. Qualitatively, our results for site preference are in agreement with previous theoretical results [16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][41][42][43][44][45][46][47]. Quantitatively, the values of E corr chem reported here may be more reliable, and in particular the relative values of E corr chem at different sites on the same metal may be important for interpreting how chemisorption evolves with coverage.…”
Section: Resultssupporting
confidence: 91%
“…The values for d N−O and other aspects of the optimized NO/metal geometries using O PSP 1 are presented in Table II. For each metal surface and site, d N−O is up to 3.4% shorter than literature values for studies employing ultrasoft pseduoptoentials [32,33,[35][36][37][38][39], supporting systematic disagreement in d N−O between the two pseudoptoential approximations. For all metals, as expected, d N−O increases with increasing NO-metal coordination.…”
Section: Resultsmentioning
confidence: 62%
“…on well-defined metal surfaces has been researched extensively in recent years due to the fundamental interest and practical applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In the case of Nb surfaces, the high-resolution electron energy loss spectroscopy (HREELS) has been used early to explore the adsorption of NO on the Nb(1 1 0) surface by Bartke et al [18] They found that parts of NO molecules adsorbed on the metal surface stably, while parts of NO molecules were dissociated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for NO on Rh(111) it has been demonstrated that in ordered structures with both top and threefold bound adsorbates, only the top bound adsorbates are detected by the STM tip. 14 Furthermore, CO is in general difficult to image in STM due to its high mobility. The interaction with the STM tip may cause the CO molecules to switch site, or the molecules may move spontaneously from one site to another during the time span that is required to record a full STM image.…”
Section: Introductionmentioning
confidence: 99%